World Development Report 1986 - World Bank; World Bank. (Washington, D.C. The World Bank, 1986)
This is the ninth in an annual series assessing development issues. The world economy is entering its fourth year of growth since the recession of 1982. Yet the recovery is hesitant with many developing countries facing serious problems of adjustment. The recent decline in oil prices, interest rates, and inflation will provide a stimulus to developed and developing countries alike. But many debtor countries, particularly oil exporters, will find it hard to maintain growth in the near term. The effects of the recovery have been much weaker for many low-income Sub-Saharan countries. Part I of the report explores the policies required to restore growth in the developing world. It stresses the importance of developed countries maintaining the policies that have both reduced inflation and moderated distortions in their markets. Of concern however is the increase in international trade restrictions, if countries are to attain sustainable growth, the reform of domestic institutions must be accompanied by an effort towards international freer trade. Part 2 suggests that the gradual liberalization of trade should be a high priority for international action in agriculture. An examination of the policy options in developing countries suggests that economic stability and growth could be greatly enhanced by focusing on improved pricing and trade policies.
Electronic reproduction.
Keywords: Economic assistance; Underdeveloped areas -- Economic conditions; Underdeveloped areas -- Economic indicators; Electronic books